Low-Dose Gemcitabine Treatment Enhances Immunogenicity and Natural Killer Cell-Driven Tumor Immunity in Lung Cancer - Zhang, Xin; Wang, Dong; Li, Zhidong; Jiao, Defeng; Jin, Linlin; Cong, Jingjing; Zheng, Xiaohu; Xu, Lijun (Frontiers in Immunology, 2020)
Gemcitabine has been used as first-line chemotherapy against lung cancer, but many patients experience cancer recurrence. Activation of anti-tumor immunity in vivo has become an important way to prevent recurrence. Anti-tumor immune responses are often dependent upon the immunogenicity of tumors. In our study, we observed that low-dose gemcitabine treatment enhanced the immunogenicity of lung cancer by increasing the exposure of calreticulin, high mobility group box 1 and upregulating expression of NKG2D ligands. Further studies demonstrated that low-dose gemcitabine treatment increased interferon-γ expression and NK-cell activation in mice. Low-dose gemcitabine treatment was sufficient for inhibiting tumor growth with few side effects in vivo. These data suggest that low-dose gemcitabine-induced immunochemotherapy activated antitumor immunity in immunocompetent patients.